Quoted:

WTF. I shouldn't be having any problem with this simple pre-algebra problem and yet...my head is full of fuck.

-7 = b - (-7)

Here's where I'm at. I just know I'm wrong.

original problem: -7 = b - (-7)

Well Your frist problem is your problem set up. -7=b-(-7) Lets multiply each side by -1.

Now we have 7=b+(+7). Next we will a first and scond derivative. b` and b``.

7+b`+b``=b+(+7)+b`+b``. If you've gone far enough in math you;d recognize this is actually the formula for intersecting planes on a cartesian coordinate graph, and thus can be written as x+y+z=b. So now we do some math and com eup with this.

7+(z+y+x)`+x+y+z)``=e^(-2t)cos(t)+e^(-2t)+sin(t)

Well we all know that cos+sin=1. So I will factor them out.

7+(x+y+z)`+(x+y+z)``=e^(-2t)

From physics we know e=~2.71 and t is the solar cyclical gravitiational constant of 1.76*10^-27.

Well we also know that planes on a cartesian graph intersect only at points in wave lengths where the strong force and the weak force peak and vally at the same time, and thus cancel eachother out. When you add them up, x+y+z=b.

So now we are back to 7+b`+b``=e^(-2t). Well when we graph out e^(-2t) we will see sinusodial waves that get bisected to the normal planes of b` and b``. So no we can cancel out b` and b``.

Now we are at 7=e^(-2t) Because of the constants mentioned earlier, the law of conservation of angular momentum, and advanced kienamatics, we know that e^(-2t) can also be re-written as -b/2. When you solve for b, you now have b=-14.